(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Lineament are extended mappable linear or curvilinear feature of a surface which can be utilized in mineral, oil, gas, and underground water studies. They are obvious in satellite images, aerial images or aerial photographs. The aim of this study is to analyse an automatically generated lineament from part of the Maru schist belt using a combination of Digital Elevation Model (DEM) data and Aeromagnetic data. The area of study is within the Maru schist belt in Zamfara State. A shaded relief map was produced from the two data sources and the lineament was extracted automatically from them. The extracted lineament was combined to obtain a final lineament map of the area. Trends such as N-S, NW–SE, ENE–WSW and NW–SE, with very little E-W were all present. The areas of very high, high, moderate and low population of lineaments was delineated. Regions with very high lineament intersections and lineament concentration, covers an area of 153.6 km2 and accounts for 16.1% of the study area, these regions are known to harbour gold and iron ores from literature reviews. These target regions are located at the Northern and South part of the study area. Also, the gold artisan miners have dominated these same regions and they have only started from exposed vein of gold mineralization. With this rather fast and easier approach of obtaining such a map, it could be used as a start point for planning a more detailed geophysical or geological survey